Analysis of Increasing Non-Aeronautical Business Targets at Terminal 3 of Soekarno-Hatta International Airport - Danus Winarko; Juliater Simarmata; Primadi Candra Susanto (Dinasti International Journal of Digital Business Management, 2024)
The analysis article on increasing non-aeronautical business targets at Terminal 3 of Soekarno-Hatta International Airport is in the domain of strategic management science. The aim of this research is to formulate a hypothesis regarding the interrelationship of various aspects, which will then be used as a basis for further research in the field of strategic management. This research uses a qualitative descriptive research methodology. The data used in this research comes from previous research which is still relevant to this research. Information is collected from leading scientific online platforms, such as Publish or Perish, Google Scholar, digital reference books, and the journal Sprott. The results obtained from this research are presented as follows: 1) Passenger waiting time influences the Non Aeronautical Business target at Terminal 3 of Soekarno-Hatta International Airport; 2) The passenger departure process influences the Non-Aeronautical Business target at Terminal 3 of Soekarno-Hatta International Airport; and 3) Tenant selection influences the Non Aeronautical Business target at Terminal 3 of Soekarno-Hatta International Airport.